Point-of-Use Mixing of Influenza H5N1 Vaccine and MF59 Adjuvant for Pandemic Vaccination Preparedness: Antibody Responses and Safety. A Phase 1 Clinical Trial. (18th November 2014) - Mulligan, Mark J.; Bernstein, David I.; Frey, Sharon; Winokur, Patricia; Rouphael, Nadine; Dickey, Michelle; Edupuganti, Srilatha; Spearman, Paul; Anderson, Edwin; Graham, Irene; Noah, Diana L.; Mangal, Brian; et al.
Abstract: Background.  Avian influenza A/H5N1 has threatened human health for nearly 2 decades. Avian influenza A vaccine without adjuvant is poorly immunogenic. A flexible rapid tactic for mass vaccination will be needed if a pandemic occurs. Methods.  A multicenter, randomized, blinded phase 1 clinical trial evaluated safety and antibody responses after point-of-use mixing of influenza A/Indonesia/05/2005 (H5N1) vaccine with MF59 adjuvant. Field-site pharmacies mixed 3.75, 7.5, or 15 mcg of antigen with or without MF59 adjuvant just prior to intramuscular administration on days 0 and 21 of healthy adults aged 18–49 years. Results.  Two hundred and seventy subjects were enrolled. After vaccination, titers of hemagglutination inhibition antibody ≥1:40 were achieved in 80% of subjects receiving 3.75 mcg + MF59 vs only 14% receiving 15 mcg without adjuvant ( P < .0001). Peak hemagglutination inhibition antibody geometric mean titers for vaccine + MF59 were ∼65 regardless of antigen dose, and neutralizing titers were 2- to 3-fold higher. Vaccine + MF59 produced cross-reactive antibody responses against 4 heterologous H5N1 viruses. Excellent safety and tolerability were demonstrated. Conclusions.  Point-of-use mixing of H5N1 antigen and MF59 adjuvant achieved target antibody titers in a high percentage of subjects and was safe. The feasibility of the point-of-use mixing should be studied further.